Influence of Promotion Strategies and Pricing on Purchasing Decisions of Raw Plastic Pellet Products at PT. Bahkti Jaya Kusuma in Gading Serpong, South Tangerang City - Abdurohman, Dede (Sinergi International Journal of Management and Business, 2023)
This research aims to determine the influence of promotion strategies and pricing, both partially and simultaneously, on purchasing decisions. The population consists of consumers who buy products at PT. Bahkti Jaya Kusuma, with a sample size of 100 consumers. The data analysis methods used include multiple linear regression analysis, the product-moment correlation coefficient, the coefficient of determination, and significance tests. The analysis results show an influence, both partially and simultaneously, on purchasing decisions. The multiple linear regression coefficient results are obtained as Y = 5,251 + 0.517 X1 + 0.057 X2 + e. The product-moment correlation coefficient yields a value of r = 0.852. The coefficient of determination results in an R-squared value of 72.6%. The F-test results indicate a calculated F value > the tabulated F value, namely 128.291 > 4.00.